Reactions of Organotin (IV) Compounds with Platinum Complexes Part (I) : Oxidative-Addition Reaction of SnRxCl4-x with [Pt(PR3')n], R' = Et, n = 3 or 4 and R' = Cyc, n = 2 - A.K. Al-Allaf, Talal (Asian Journal of Chemistry, 2010)
The complex [Pt(PEt3)n] (n = 3 or 4) reacts oxidatively with SnR2Cl2 (R = Me, Et) to give trans-[PtCl(SnR2Cl)(PEt3)2] which may also be obtained by treatment of [Pt(C2H4)(PPh3)2] and SnR2Cl2 followed by addition of two molar equivalents of PEt3. The corresponding reaction of SnPh2Cl2 likewise gives the product of insertion of Pt(0) into Sn-Cl bonds when the reaction was carried out at –3DºC, but at room temperature the product of insertion into the Sn-Ph bond is obtained. Tin compounds SnR3Cl (R = Me, Ph) give product of insertion into Sn-R bonds at room temperature, but only SnMe3Cl gives product of insertion into Sn-Cl bonds at –3DºC. The compounds SnPh4 and SnPh3Me undergo insertion into Sn-Ph bonds to form both the cis- and trans- isomers. The dinuclear tin compound Sn2Ph6 reacts with [Pt(PEt3)4] to give the complexes trans-[Pt(SnPh3)2(PEt3)2] and cis- and trans-[PtPh(SnPh3)(PEt3)2], while its reaction with [Pt(C2H4)(PPh3)2] followed by addition of an equimolar quantity of PEt3 gives cis- and trans-[PtPh(Sn2Ph5)(PEt3)2] along with the breakdown products cis- and trans-[PtPh(SnPh3)(PEt3)2]. Similar observations were made for the reaction of [Pt(PCyc3)2] with SnR2Cl2 (R = Me, Et, Bu, Ph) to give trans-[PtCl(SnR2Cl)(PCyc3)2], with SnR3Cl (R = Me, Bu, Cl) to give trans-[PtCl(SnR3)(PCyc3)2], and with SnPh3Cl to give cis- and trans-[PtPh(SnPh2Cl)(PCyc3)2]. The reactions of the lead compounds PbR3Cl (R = Me, Ph) with [Pt(PCyc3)2] were found to proceed analogously. The compound PbMe3Cl gives the product of insertion into Pb-Cl bonds whereas PbPh3Cl gives product of insertion into Pb-Ph bonds as SnR3Cl compounds do. The complexes and their decomposition products were identified by 31P NMR spectroscopy.